Change and continuity management in the public sector : the DALI model for effective decision making - Gonzi, Rebecca Dalli (Emerald Publishing, 2019)
In evolving crises, managing teams often have little information and fewer resources. This book proposes a model for more effective decision making early in the evolution of a crisis, before disaster response plans are activated.